The Induction of Bone Formation: The Translation Enigma - Klar, Roland M. (Frontiers in Bioengineering and Biotechnology, 2018)
A paradigmatic shift in the way of thinking is what bone tissue engineering science requires to decrypt the translation conundrum from animal models into human. The deductive work of Urist (1965), who discerned the principle of bone induction from the pioneering works of Senn, Huggins, Lacroix, Levander, and other bone regenerative scientists, provided the basis that has assisted future bone tissue regenerative scientists to extend the bone tissue engineering field and its potential uses for bone regenerative medicine in humans. However, major challenges remain that are preventing the formation of bone by induction clinically. Growing experimental evidence is indicating that bone inductive studies are non-translatable from animal models into a clinical environment. This is preventing bone tissue engineering from reaching the next phase in development. Countless studies are trying to discern how the formation of bone by induction functions mechanistically, so as to try and solve this enigmatic problem. However, are the correct questions being asked? Why do bone inductive animal studies not translate into humans? Why do bone induction principles not yield the same extent of bone formation as an autogenous bone graft? What are bone tissue engineering scientists missing? By critically re-assessing the past and present discoveries of the bone induction field, this review article attempts to re-discover the field of bone formation by induction, identifying some key features that may have been missed. These include a detailed library of all proteins in bones and their arrangement in the 3D superstructure of the bone together with some other important criteria not considered by tissue engineering scientists. The review therefore not only re-iterates possible avenues of research that need to be re-explored but also seeks to guide present and future scientists in how they assess their own research in light of experimental design and results. By addressing these issues bone formation by induction without autografts might finally become clinically viable.